(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
While the democratic paradigm of governance and its constituent political processes are well established in Australia, consistently negative media representations of people seeking asylum may be viewed as justification for institutional decisions allowing continued punitive treatment of people seeking asylum on Australian shores. Historically, notions of Australian sovereignty exist as a changing discourse with reference to land claims and the Australian Indigenous population (O’Dowd 2011; Due 2008). However, in terms of contemporary political claims about Australia’s need to enforce border protection policies, notions of sovereignty are consistently framed through the themes, images and language of military discourses. Media scholar, John Street suggests that although there is disagreement about whether specific political outcomes can be attributed to press influence, the role of television in politics has been more comprehensively established as shaping broader world views in regards to ideas, values and practices that are considered ‘common-sense’ (Street 2011; Craig 2013). This paper argues that the increasing role of the military in the treatment and processing of people seeking asylum may be justified, through repetitive negative media representations of asylum seekers which secures public support for such practices, thereby undermining the very principles of the democratic paradigm, and indeed the role of the media or ‘fourth estate’(Schultz 1998) in a functioning democracy.